DNA Polymerase Fidelity: Comparing Direct Competition of Right and Wrong dNTP Substrates with Steady State and Presteady State Kinetics - Bertram, Jeffrey G. (2010)
DNA polymerase fidelity is defined as the ratio of right (R) to wrong (W) nucleotide incorporations when dRTP and dWTP substrates compete at equal concentrations for primer extension at the same site in the polymerase-primer-template DNA complex. Typically, R incorporation is favored over W by 10(3) – 10(5), even in the absence of 3′-exonuclease proofreading. Straightforward in principal, a direct competition fidelity measurement is difficult to perform in practice because detection of a small amount of W is masked by a large amount of R. As an alternative, enzyme kinetics measurements to evaluate k(cat)/K(m) for R and W in separate reactions are widely used to measure polymerase fidelity indirectly, based on a steady-state derivation by Fersht. A systematic comparison between direct competition and kinetics has not been made until now. By separating R and W products using electrophoresis, we have successfully made accurate fidelity measurements for directly competing R and W dNTP substrates for 9 of the 12 natural base mispairs. We compare our direct competition results with steady state and presteady state kinetic measurements of fidelity at the same template site, using the proofreading-deficient mutant of Klenow Fragment (KF(−)) DNA polymerase. All the data are in quantitative agreement.